2015
DOI: 10.1248/bpb.b15-00043
|View full text |Cite
|
Sign up to set email alerts
|

SEW2871 Alleviates the Severity of Caerulein-Induced Acute Pancreatitis in Mice

Abstract: Sphingosine-1-phosphate type-1 receptor (S1P1) agonists have the potential to inhibit the egress of lymphocytes, and have been demonstrated to provide protective effects on some acute inflammatory diseases. However, the value of S1P1 agonists on acute pancreatitis (AP) remains unclear. The aim of this study was to explore the effect of SEW2871, a S1P1-selective agonist, on caerulein-induced AP in mice. AP was induced by giving eight intraperitoneal injections of caerulein (50 µg/kg/h) at hourly intervals. SEW2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In sham groups, there were no significant differences between vehicle and SEW2871 groups. (AST at 4h: 31 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] As shown in Figure 2A, IRI livers mostly demonstrated sinusoidal vascular congestion at 4 h; however, livers treated with SEW2871 showed suppressed congestion at 4 h. after IRI. IRI livers treated with only vehicle were mostly characterized by sinusoidal vascular congestion, whereas IRI livers with SEW2871 showed suppressed congestion at 4 h (panel A).…”
Section: Sew2871 Ameliorates Hepatocellular Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In sham groups, there were no significant differences between vehicle and SEW2871 groups. (AST at 4h: 31 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] As shown in Figure 2A, IRI livers mostly demonstrated sinusoidal vascular congestion at 4 h; however, livers treated with SEW2871 showed suppressed congestion at 4 h. after IRI. IRI livers treated with only vehicle were mostly characterized by sinusoidal vascular congestion, whereas IRI livers with SEW2871 showed suppressed congestion at 4 h (panel A).…”
Section: Sew2871 Ameliorates Hepatocellular Injurymentioning
confidence: 99%
“…The development of the highly selective S1PR1 agonist, SEW2871, which was originally identified in 2004, 8 has enabled examination of S1PR1-mediated cell responses, using animal models such as renal IRI, 9,10 myocardial IRI, 11 heart transplant, 12 cardiopulmonary bypass, 13 and acute pancreatitis. 14 Using a renal IRI mouse model, Lien et al 9 revealed that SEW2871 administration significantly attenuated renal damage by reducing neutrophil/macrophage infiltration and cytokine production in the kidney. In hepatic IRI models, however, there have been few studies on the effect of selective S1PR1 agonists.…”
Section: Introductionmentioning
confidence: 99%